Pengaturan Kepemilikan Tanah Berdasarkan Hukum Pertanahan dan Implementasinya - Gita Silva Pramesti (Savana, 2024)
Land has a very important role in the lives of all communities, such as its role as a place to live, plantation businesses, agricultural businesses, mining businesses, and so on. Some of the problems that often occur in Indonesian society are unequal ownership or control of land, land control without permission, problems related to land acquisition for development purposes to which those entitled or authorized. The aim of this research is to in-depth analyze aspects of land law from a legal perspective, using a case study of the Jakarta PTUN decision letter number 145/G/TF/2023/PTUN.JKT as the focus. The main objective is to identify and evaluate the implementation of land regulations in these concrete cases, as well as understand their impact on land law more broadly. This research method uses normative legal analysis methods and case studies. A normative legal analysis approach is used to evaluate the legal framework relevant to land, while the case study refers to the Jakarta PTUN decision letter number 145/g/tf/2023/ptun.jkt as the object of analysis. The data used in this research was obtained through a review of legal documents, such as laws, regulations and related court decisions. The results of the research are based on the analysis of the Jakarta PTUN decision number: 145/g/tf/20023/ptun.jkt, it can be concluded that the panel of judges stated that they rejected the plaintiff's lawsuit, because the plaintiff had misinterpreted the letter as a decision of Tun officials which actually only contained information. of a general nature regarding the blocking application submitted by the plaintiff to the defendant